The The Relationship of Leg Muscle Strength on Dynamic Balance among Elderly - Kadek Liza Widya Astari; I Putu Prisa Jaya; I.A Pascha Paramurthi (Universitas Udayana dan Diaspora Taipei Medical University, 2021)
Background: Elderly is someone who has reached the age of 60 years and over. Along with increasing age, a person will experience physical changes in the musculoskeletal system, which causes a decrease in the number of muscle fibers and muscle mass. This can result in a decrease in muscle strength, especially in the leg muscles, which is one of the factors that can affect the balance of the human body. The decreased dynamic balance will result in the risk of injury in the elderly. Objective: The aim of this study was to prove the relationship of leg muscle strength and dynamic balance in the elderly. Methods: The design of this study was a cross sectional study conducted in April 2021 with a population of all elderly people in Banjar Jasan, Desa Sebatu, Kecamatan Tegalalang, Kabupaten Gianyar, that met the inclusion and exclusion criteria, so that 46 samples were obtained. Measurement of muscle strength using a Leg Dynamometer and dynamic balance using the TUG test. Data analyzed using computer software, namely the Pearson test to determine the relationship of leg muscle strength and dynamic balance. Results: The results showed that from 46 elderly there was a relationship of leg muscle strength and dynamic balance using the Pearson test with p results of 0.001 (p < 0.05) with a correlation coefficient of -0.819 (r > 0.05) which indicates a very strong correlation. Conclusion: It can be concluded that there is a very strong and negative relationship between leg muscle strength and dynamic balance in the elderly.